Exploring the relationship between language, culture and identity - Lee, Su Kim (Penerbit UKM, 2003)
This paper will explore the interconnectedness of language and culture, and how language and culture impact upon one’s identity. It will first define the three constructs – language, culture and identity. This will be followed by an overview of the work of social theorists and educationists. The paper will then present a review of literature of research studies in the field. Recent studies on the interplay of language and culture and its impact on social and cultural identity in the field of Second Language Acquisition will be highlighted. Lastly the paper concludes with a discussion of recent research studies on language and identity in the Malaysian context.